Implementation of the Right to Education of Persons from the Temporarily Occupied Territories of Ukraine: Administrative and Legal Challenges - Minka, Tetyana; Badak, Maksym (Problems of legality, 2026)
The armed aggression against Ukraine has resulted in the prolonged occupation of part of its territory and large-scale internal displacement of the population. Under these conditions, a significant number of children and young people from the temporarily occupied territories and internally displaced persons face difficulties in exercising their right to education within the Ukrainian educational system. Purpose of the study is to conduct a comprehensive analysis of the administrative and legal framework for ensuring the implementation of the right to education of internally displaced persons and citizens residing in the temporarily occupied territories of Ukraine, as well as to identify key problems and develop proposals for their resolution. The study applies the formal legal method to analyze the content of legal norms in the field of education and determine their place within the system of administrative law. The system structural method is used to examine the mechanism for implementing the right to education as an integrated system of interconnected elements. The logical legal method is applied to formulate generalizations and conclusions. The methods of analysis and synthesis are used to combine theoretical approaches with law enforcement practice and to develop proposals for improving current legislation. The study establishes that the current system of administrative and legal support for the implementation of the right to education for these categories of persons is characterized by several organizational and procedural problems. These include difficulties in access to educational procedures, insufficient flexibility in the mechanisms for recognition of learning outcomes, and uneven application of state guarantees among educational institutions. The need to improve admission procedures, mechanisms for recognizing learning outcomes, and opportunities for distance and external forms of education is substantiated. The study proposes directions for improving administrative and legal regulation aimed at increasing access to education for persons from the temporarily occupied territories and internally displaced persons.